Investigation of the Adsorption Rubraca Anticancer Drug on the CNT(4,4-8) Nanotube as a Factor of Drug Delivery: A Theoretical Study Based on DFT Method - Sheikhi, Masoome; Shahab, Siyamak; Khaleghian, Mehrnoosh; Ahmadianarog, Mahin; Azarakhshi, Fatemeh; Kumar, Rakesh (Current Molecular Medicine, 2019)
Background: In the present study, the interaction between new drug Rubraca and CNT(4,4-8) nanotube by Density Functional Theory (DFT) calculations in an aqueous medium for first time have been investigated. Method and Results: According to calculations, the intermolecular hydrogen bonds take place between active positions of the molecule Rubraca and hydrogen atoms of the nanotube that plays an important role in the stability of the complex CNT(4,4- 8)/Rubraca. The non-bonded interaction effects of the molecule Rubraca with CNT(4,4- 8) nanotube on the electronic properties, chemical shift tensors and natural charge have been also detected. The natural bond orbital (NBO) analysis suggested that the molecule Rubraca as an electron donor and the CNT(4,4-8) nanotube plays the role an electron acceptor at the complex CNT(4,4-8)/Rubraca. The electronic spectra of the Rubraca drug and the complex CNT(4,4-8)/Rubraca were also calculated by Time Dependent Density Functional Theory (TD-DFT) for the investigation of adsorption effect of the Rubraca drug over nanotube. Conclusion: The use of CNT(4,4-8) nanotube for Rubraca delivery to the diseased cells have been established.
Keywords: Electronic spectra